Pengaruh debt to asset ratio , rasio kas, size, return on asset, growth dan kepemilikan institusional terhadap dividend payout ratio pada sektor perbankan - STEVANIUS STEVANIUS; STEVEN YAP (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this study is to analyze and obtain empirical evidence of the effect of debt to asset ratio, cash ratio, size, return on assets, growth, and ownership Institutional dividend payout ratio. The objects used in this study is the banking sector listed in Indonesia Stock Exchange from the period 2008-2014. The sample consisted of eight companies which have been selected by purposive sampling method and analyzed using Eviews8 with multiple linear regression and random effect models to test the hypothesis. This study shows that the debt to asset ratio has an influence on the dividend payout ratio while the cash ratio, size, return on assets, growth, and institutional ownership has no effect on the dividend payout ratio. Overall, the independent variables have an effect simultaneously to the dividend payout ratio.